2012
DOI: 10.1002/pen.23445
|View full text |Cite
|
Sign up to set email alerts
|

Effect of EPDM‐g‐MAH on the morphology and properties of PA6/EPDM/HDPE ternary blends

Abstract: The formation of core‐shell morphology within the dispersed phase was studied for composite droplet polymer‐blend systems comprising a polyamide‐6 matrix, ethylene‐propylene‐diene terpolymer (EPDM) shell and high density polyethylene (HDPE) core. In this article, the effect of EPDM with different molecular weights on the morphology and properties of the blends were studied. To improve the compatibility of the ternary blends, EPDM was modified by grafting with maleic anhydride (EPDM‐g‐MAH). It was found that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…A similar conclusion can be drawn not only in IPC, but also in other systems [16e19]. Yang et al [16,17] found the impact strength of PA6/EPDM-g-MA/HDPE blends with coreeshell dispersed phase greatly increased, compared with other structure (dispersed separately or partial capsulation structure). Wilkinson et al [18] regarded that the coreeshell PA6/SEBS particles in PP matrix resulted in a huge increase in charpy impact strength with respect to other toughened PP.…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…A similar conclusion can be drawn not only in IPC, but also in other systems [16e19]. Yang et al [16,17] found the impact strength of PA6/EPDM-g-MA/HDPE blends with coreeshell dispersed phase greatly increased, compared with other structure (dispersed separately or partial capsulation structure). Wilkinson et al [18] regarded that the coreeshell PA6/SEBS particles in PP matrix resulted in a huge increase in charpy impact strength with respect to other toughened PP.…”
Section: Introductionsupporting
confidence: 51%
“…It is interesting that the melting peak at about 120 C for the samples crystallized non-isothermally appears a weak composition dependence: it drops with the decrease of EbP component. Located in the core of coreeshell particles, PE chains in EbP can fold in pure ethylene chains environment due to utter incompatibility of EPR/PE [16,29]. Higher EbP content in blends offers greater concentration of PE so that nucleation and crystallization behavior are enhanced easily.…”
Section: Crystallization and Melting Behaviormentioning
confidence: 98%
“…This model has been used frequently by researchers for the prediction of the morphology of ternary blends. [3][4][9][10][11][12][13][14] It is worth mentioning that there is another complex morphology that has received less attention. It consists of the core-shell morphology together with dispersed particles of the shell-forming component.…”
Section: Introductionmentioning
confidence: 99%
“…Downloaded by [Stony Brook University] at 10:23 02 November 2014 Furthermore, it is recognized that there is a close correlation between the morphology and mechanical properties of ternary blends. This relationship is of current interest to a number of researchers [e.g., [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation